The protection of the accused in international criminal law according to the human rights law standard - Kremens, Karolina (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The presented paper discusses the influence of international human rights law on international criminal law. It tries to give an answer to the question of whether rules protecting the accused in international criminal proceedings meet the human rights law standard provided by international declarations and covenants. Meaning, if the proceedings before the International Criminal Tribunal for Former Yugoslavia (ICTY), International Criminal Tribunal for Rwanda (ICTR) and International Criminal Court (ICC) meet the standard provided by international human rights law, in particular the International Covenant on Civil and Political Rights. The paper proves that international human rights law has affected international criminal law tremendously. Moreover, it is argued that the protection of the accused in the law of the international courts and tribunals with regard to his rights has improved when compared to the international human rights law standard. In particular the Rome Statute of the ICC provides the accused with the most comprehensive protection. This is especially visible in the case of such rights as the presumption of innocence, right to an interpreter and right to remain silent. Nevertheless, some shortcomings in the law of the ad hoc tribunals and ICC can be observed, in particular when it comes to identifying the commencement of protection of the accused.
Keywords: międzynarodowe prawo karne; prawa człowieka; ochrona oskarżonego